Fragmentasi Pemberontak Dan Durasi Perang Sipil: Thailand Selatan Pasca Dimediasi Organisasi Kerjasama Islam - Yurisa Irawan (Andalas Journal of International Studies (AJIS), 2019)
Southern Thailand violent conflict, a civil war faced by Thailand Government against Pattani groups, has been lasted since 2004 without significant reconciliation.International organization, i.e., Organization of Islamic Conference (OIC) has participated as the third actor striving for resolution. However, the conflict has been trapped in stagnancy. This study examines how three involving actors contributes to civil war duration. Third parties’ incapabilities, rebel fragmentation, and state’s power are the main reason why such a civil conflict could not reach a mutual agreement. Such conclusion is deduced based on qualitative data through two frameworks: Hourglass model and bargaining theory.